2014
DOI: 10.21083/partnership.v9i1.2990
|View full text |Cite
|
Sign up to set email alerts
|

Research Data Management and the Canadian Academic Library: An Organizational Consideration of Data Management and Data Stewardship

Abstract: Research data management (RDM) has become a professional imperative for Canada's academic librarians. Recent policy considerations by our national research funding agencies that address the ability of Canadian universities to effectively manage the massive amounts of research data they now create has helped library and university administrators recognize this gap in the research enterprise and identify RDM as a solution. RDM is not new to libraries, though. Rather, it draws on existing and evolving organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…Já no Canadá, Steeleworthy (2014) destacou que a gestão de dados de pesquisa tornou-se uma prática exigida às bibliotecas acadêmicas, principalmente devido a exigências presentes em políticas estabelecidas por agências nacionais de financiamento à pesquisa. Por conseguinte, foi necessário que tais bibliotecas ampliassem o rol de serviços que já desempenhavam, incorporando atividades relacionadas à coleta, à catalogação, ao acesso, ao arquivamento, à preservação e à referência de dados de pesquisa.…”
Section: Política E Plano De Gestão De Dados De Pesquisaunclassified
See 1 more Smart Citation
“…Já no Canadá, Steeleworthy (2014) destacou que a gestão de dados de pesquisa tornou-se uma prática exigida às bibliotecas acadêmicas, principalmente devido a exigências presentes em políticas estabelecidas por agências nacionais de financiamento à pesquisa. Por conseguinte, foi necessário que tais bibliotecas ampliassem o rol de serviços que já desempenhavam, incorporando atividades relacionadas à coleta, à catalogação, ao acesso, ao arquivamento, à preservação e à referência de dados de pesquisa.…”
Section: Política E Plano De Gestão De Dados De Pesquisaunclassified
“…Por esta razão, Steeleworthy (2014) ressaltou a importância das bibliotecas acadêmicas estabelecerem parcerias com pesquisadores, conselhos de ética de pesquisa, grupos de pesquisa e outras bibliotecas. Nesse sentido, é fundamental uma postura multifacetada do bibliotecário na qual reiteram-se ações e serviços colaborativos entre bibliotecários de diversos campus das universidades (Steeleworthy, 2014).…”
Section: Política E Plano De Gestão De Dados De Pesquisaunclassified
“…Policy formulations and institutional road maps such as sharing data curation centres and services and the management of project data in archives and repositories such as copyright were also found. Steeleworthy (2014) examined RDM policy services in academic libraries in Canada. The findings revealed that the organisational structure, collection development, preservation, archives, reference, and research as key components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For academic institutions, university libraries play a critical role not only in managing research data but also in training the next generation of researchers to be well versed in data management practices (Koltay, 2019; Tenopir et al, 2016). There exists a knowledge gap among scientists that can easily be addressed by these professionals (Steeleworthy, 2014; Strasser and Hampton, 2012; Tenopir et al, 2017; Verbakel et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%